Determinações políticas na produção científica da Ciência da Informação do Brasil: Impacto da Tabela de Áreas de Conhecimento (TAC) do CNPq - De Sales, Rodrigo [UNESP]; Murguia, Eduardo Ismael (My University, 2015)
The development of Information Science, although mainly studied under a perspective guided by the aspects related to the object itself (information), also suffers external influences determined by the governments' political actions. In Brazil, the Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq) is a federal agency responsible for the actions that foster national scientific research. Having Foucault's concept of governmentality and Habermas's concept of rationality as a background, we aim to explain the government institutions in Brazil regarding the area of production and organization of scientific knowledge, specifically those connected to the articulation of the areas of Information Science, Library Science and Archival Science. To do so, we adopted as our analysis object one of the main political devices drawn up by the CNPq - the Knowledge Area Table. We conclude that, although the table serves as an efficient scientific and university management tool, it creates shortcomings regarding the political interference on theories and practices of areas that are considered tradionally well-established.
Political determinations in the scientific production of information science in Brazil: Impact of the classification of knowledge areas of the CNPq
Keywords: Archival science; Brasil; CNPq; Information science; Knowledge organization; Library science; Table of knowledge areas of the CNPq